Complexos agroindustriais e sua influência na Farm Bill de 2014 - Rodrigues, Isabela Almeida (2023)
This work investigates the ethanol lobby on the American agricultural law, the Farm Bill, of 2014. The formation of the ethanol agro-industrial complex usually engages in the construction of arrangements between actors according to the best combination that helps them achieve their interests in agricultural laws. The role of the State is fundamental in this conformation: it is in its interest that the Farm Bills are perpetuated, as these laws help in the economic maintenance of the country. This situation occurs in a specific context that allows for re-election, international trade and lobbying. It is in this scenario that the influence of certain agents on public policies occurs. Thus, the objective is to understand the formulation of the 2014 Farm Bill, in addition to the aspects that influence its votes and how financing contributes to politicians continuing to vote in favor of these laws. To achieve this, in the research we will use the process-tracing method explaining outcome PT. The hypothesis is that the ethanol agro-industrial complex, through lobbying among actors interested in maintaining Farm Bills, influenced the formation of the 2014 law's agenda. As a result, it was possible to debate the theories used, in addition to collecting data regarding the law, and analyze the viability of the hypothesis. Finally, we conclude that there is interaction between different actors, in accordance with the hypotheses of the Advocacy Coalition Framework and the Agroindustrial Complex theory, which guided the agenda and approval of the 2014 Farm Bill